TEAMS GAME TOURNAMENT (TGT): A LEARNING MODELS TO IMPROVE MOTIVATION OF STUDENTS IN LEARNING MATHEMATICS - Rika Wulandari (Literasi Nusantara, 2020)
This study aims to increase the motivation to learn mathematics through the use of the TGT (Teams Games Tournament) Model in fifth grade students of SDN Tanjungjati 2, Bangkalan. This type of research is a collaborative classroom action research model using the Kemmis and Mc Taggart cycle model. The subjects of this study were fifth grade students of SDN Tanjungjati 2, Bangkalan. This classroom action research was conducted in 2 cycles. Data collection techniques using observation and questionnaires. The criteria for the success of this action research were the suitability of the teacher to apply the TGT learning model and the percentage of student motivation to reach ? 75%. The results showed that the TGT learning model could increase the learning motivation of grade V SDN Tanjungjati 2, Bangkalan. The learning is to get a learning experience, name the material, demonstrate the results, repeat the material, and celebrate success. In the pre-cycle, the students' average motivation to learn mathematics obtained a percentage of 54.60%. After being given the action, it increased to 68.40% at the end of cycle I, and at the end of cycle II increased to 95.60%.